Journalism in a state of flux: journalists as agents of technology innovation and emerging news practices - Matsiola, Maria; Veglis, Andreas A.; Spyridou, Lia Paschalia; Kalliris, George; Dimoulas, Charalambos (My University, 2013)
The move to a networked media environment presents a range of challenges for journalistic roles, norms and daily practices. This article employs actor network theory to investigate how different actors negotiate and ultimately shape the manner in which the internet and related digital technologies are embedded in the newsroom. Findings suggest that professional culture - articulated in skills, ideas and practices - acts as a network that weakens the potential impact of technology towards innovation and audience-oriented models of journalism. The results point to the conclusion that the internet and related tools are seen as empowering journalists to do their (traditional) jobs better instead of moving on to the next stage built around a stronger commitment to capitalize on the growing sociotechnical potential.
Keywords: Actor-network theory; Journalism; Open access publishing